CORRELATION INTERRELATION OF PSYCHOEMOTIONAL STATE OF CHILDRENWITH SOCIO-HYGIENIC FACTORS OF CARIES OCCURRENCE - L.F. Kaskova; K.M. Popyk; L.P. Ulasevych; L.D. Korovina (Український стоматологічний альманах, 2019)
Questionnaire is one of the possible ways of research in organized children's groups, which allows us to identify socio-hygienic factors of caries occurrence. Proper oral hygiene, awareness of children about this, regular preventive visits to a dentist, knowledge about the possibility of caries prevention play an important role in caries prevention. Lately, a great attention is paid to the psycho-emotional state of adult patients and especially of children due to the impact school strain and the formation of behavioral responses on them.